Effective Stateful Firewall in Software-Defined Networking - Maw, Aung Htein (International Journal of Computer Sciences and Engineering, 2019)
A firewall is a critical security appliance for the mitigation of the security attacks not only in the traditional network, but also in software-defined networking (SDN). Previous firewall applications over SDN controller are implemented with one of two firewall concepts: centralized firewall and distributed firewall. Centralized firewall method incurs controller overhead problem as the controller acts as a centralized firewall which maintains firewall rules and filters out the traffic. Distributed firewall method comes out the complicated firewall configuration, additional cost in rules maintenance in each switch, and less sensitive to the topology. This system proposes a firewall rules installation based on topology-aware selectively distributed stateful firewall with source-based DoS attack defense mechanism. The purpose of this system is to overcome not only the performance issues but also security issues. This paper finally shows that the stateful firewall application can not only track the TCP flow, but also reduce latency plus table lookup time up to 16% in long-lived flow and 50% in short-lived flow. Moreover, according to the security perspective, the accuracy for the DOS detection and mitigation of stateful firewall application is 98.93 % of SYN flooding attack and 92.09% for UDP flooding attack.